New Bufadienolides Isolated from the Roots of Kalanchoe daigremontiana (Crassulaceae) - Barbara Moniuszko-Szajwaj (Molecules, 2016)
An aqueous extract from the roots of Kalanchoe daigremontiana turned out to be a rich source of bufadienolides. The existing literature data relate mainly to the aerial parts of Kalanchoe but there is no information about the metabolic profile of the roots, which are also used in traditional medicine. Our investigation concerning the roots of K. daigremontiana led to the isolation and characterization of eight new bufadienolides, namely 1β,3β,5β,14β,19-pentahydroxybufa-20,22-dienolide (1), 19-(acetyloxy)-1β,3β,5β,14β-tetrahydroxybufa-20,22-dienolide (2), 3β-O-α-l-rhamno-pyranosyl-5β,11α,14β,19-tetrahydroxybufa-20,22-dienolide (3), 19-(acetyloxy)-3β,5β,11α,14β-tetrahydroxybufa-20,22-dienolide (4), 3β,5β,11α,14β,19-pentahydroxy-12-oxo-bufa-20,22-dienolide (5), 19-(acetyloxy)-3β,5β,11α,14β-tetrahydroxy-12-oxo-bufa-20,22-dienolide (6), 19-(acetyloxy)-1β,3β,5β,11α,14β-pentahydroxy-12-oxo-bufa-20,22-dienolide (7) and 1β-(acetyloxy)-3β,5β,11α,14β,19-pentahydroxy-12-oxo-bufa-20,22-dienolide (8), together with seven known compounds: 11α,19-dihydroxytelocinobufagin (9), bersaldegenin-1-acetate (10), daigredorigenin-3-acetate (11), bersaldegenin-1,3,5-orthoacetate (12), bryotoxin B (13), bryophyllin B (14) and bersaldegenin (15). The structures were established applying extensive 1D- and 2D-NMR and MS spectroscopic analyses.